Communication by the South African Reserve Bank - Arnold Segawa (Communicare)
In 2000, South Africa’s central bank, the South African Reserve Bank (SARB), adopted flexible inflation targeting as a monetary regime, and in doing so, set its inflation target at 3-6% for the headline consumer price index (Coco & Viegi, 2020). Essential to achieving this inflation target is not only clear communication of ex-post policy actions, but a clear dissemination of the SARB’s future actions. This paper examines how the SARB has been communicating, with particular emphasis on their Monetary Policy Committee (MPC) press statements between January 2000 and January 2021. The breadth of the sample space is informed by a necessity to explore changes in the SARB’s communication strategies. In particular, this study considers the role of the SARB’s MPC press releases, and given the wide span of the sample, it offers an inquiry into what has changed over the 21-year period, hence considering whether there has been more clarity in the SARB’s communication over that time. This question is answered using the Flesch and Flesch–Kincaid methods, which are widely accepted in central bank communication literature. The two methods gauge how difficult a passage in English is to understand, and are thus used to assess readability hence clarity. In evaluating central bank communications and upon surveying the data, the paper offers empirical evidence about the clarity of the SARB’s MPC meeting statements spanning over two decades, and clearly exhibiting its evolution. This study finds that SARB communications’ Flesch Reading Ease Score Computation is way above and fluctuates more than the Flesch–Kincaid Grade Level Computation, exhibiting a random fluctuation between 2000 and 2015. Therefore, despite SARB’s MPC statements exhibiting more readability, their reliance on academic words has made them more complex and difficult to understand.